2020
DOI: 10.1080/02670836.2020.1792637
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on formability of three-layer joined Al/Cu/Al sheets annealed at different temperature

Abstract: Today, the use of multi-layer sheets has expanded widely in various industries. The determination of the forming limit curve for sheets is essential. In this project, three-layer aluminium1100-copper10100-aluminium1100 sheet was produced using an explosive welding method and cold rolling up to 85% strain. Then to eliminate the rolling microstructure and create the isotropic properties and to investigate the effect of annealing temperature on formability, three-layer sheets were annealed at 350°C, 400°C, and 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Zhang et al [20] reported that the difference of hardness and yield strength between cladding and base layers would cause the change of interfacial morphology. Roostaei et al [21] adopted copper as intermediate layer to prepare aluminium/copper/aluminium trilaminar explosive welded composite plate, and the effect of annealing temperature on modelling of the composite plate was studied. However, the intermediate layer needed a certain thickness to ensure the stability in the collision process, resulting in the complexity of the welding process and the waste of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [20] reported that the difference of hardness and yield strength between cladding and base layers would cause the change of interfacial morphology. Roostaei et al [21] adopted copper as intermediate layer to prepare aluminium/copper/aluminium trilaminar explosive welded composite plate, and the effect of annealing temperature on modelling of the composite plate was studied. However, the intermediate layer needed a certain thickness to ensure the stability in the collision process, resulting in the complexity of the welding process and the waste of materials.…”
Section: Introductionmentioning
confidence: 99%